2024
DOI: 10.1109/access.2020.3019457
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Space Elements of Computer Music Production Based on VR Technology

Abstract: With the continuous development of computer technology and VR technology, computer music has become the mainstream music widely used in video, games and other major fields, and the research on computer music is becoming more and more important. At present, there are many research results about computer music software, but the research on space theory of computer music is slightly weak. In order to deeply study the space elements of computer music production, this paper takes Echo of the Wind as the research ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The root note of the music scale (Major or Minor) of a melody is estimated by fitting the notes to a music scale model. The estimated root note can then be used as the key in mode changing [12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The root note of the music scale (Major or Minor) of a melody is estimated by fitting the notes to a music scale model. The estimated root note can then be used as the key in mode changing [12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…According to the analysis, one sees the future of computer music with different fields of studies, such as the ecology mentioned in Refs. [12][13][14][15]. The artefact ecology framework is also appealing.…”
Section: Limitations and Future Outlooksmentioning
confidence: 99%
“…Audio sampling technology has evolved over several decades, not limited to modern music but also encompassing the collection of sounds from various sources, including ethnic music, world music, orchestral, jazz, and music from all corners of the globe. It has become a valuable tool for music creators and producers, especially those with budget constraints, as it offers cost-effective alternatives to folk music production (Nopparat & Narkkong, 2019;Wang & Yu, 2020;Rambarran, 2021;Shang & Wang, 2022;Deruty et al, 2022).…”
Section: Background and Rationalementioning
confidence: 99%
“…After the processing of the acoustic function, 91% of the acoustic signals can be correctly converted to the basic frequency, and 92% of the acoustic signals have no obvious acoustic signals. The study found that, whether in traditional computer music or in virtual reality technology, its timbre, timbre and timbre are made up of three parts: timbre, timbre and depth [8]. This means that music produced virtually by modern computer software can have extremely high quality, and greatly provides convenience to musicians, which is also the premise of brainwave music generation.…”
Section: The History and Meaning Of Music Productionmentioning
confidence: 99%